2016
DOI: 10.1111/ane.12695
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with life satisfaction in Parkinson's disease

Abstract: This study provides new knowledge on factors associated with LS in a PD sample, including those with late-stage PD. As the ultimate goal for PD care should be improvement in LS, the results have direct clinical implication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 45 publications
(52 reference statements)
8
64
0
Order By: Relevance
“…Based on data from the larger project [26] that this study is part of, general selfefficacy has been shown to independently contribute to life satisfaction [ 43], but not to concerns about falling [44] in people with PD. Other PD-studies have reported that selfefficacy is of importance for engagement in exercise [45] and self-management [46].…”
Section: Discussionmentioning
confidence: 96%
“…Based on data from the larger project [26] that this study is part of, general selfefficacy has been shown to independently contribute to life satisfaction [ 43], but not to concerns about falling [44] in people with PD. Other PD-studies have reported that selfefficacy is of importance for engagement in exercise [45] and self-management [46].…”
Section: Discussionmentioning
confidence: 96%
“…36,39,41,42 From these findings, the importance of implementing rehabilitation programs (physical therapies, MT, and tango intervention) based on a more positive concept of disability emerges. 36,39,41,42 From these findings, the importance of implementing rehabilitation programs (physical therapies, MT, and tango intervention) based on a more positive concept of disability emerges.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 In qualitative studies, the context for the study and the connection to a theoretical framework were reported. 41,42 In qualitative studies, the context for the study and the connection to a theoretical framework were reported.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its development in 2001, the PADLS has been used in various PD studies; see, for example, [1115]. To the best of our knowledge, its psychometric properties have only been reported in the original publication [10] and in a conference abstract [16].…”
Section: Introductionmentioning
confidence: 99%